A Multiplex Polymerase Chain Reaction Assay for the Detection of Herpes Simplex Virus, Cytomegalovirus, and Varicella-Zoster Virus in Cerebrospinal Fluid - Tatjana Luzius; Samuel D. Jeske; Julia Baer; Uta Goelnitz; Ulrike Protzer; Jochen M. Wettengel (Microorganisms)
Viral meningitis poses a significant clinical challenge due to its rapid onset and potential progression to life-threatening encephalitis. Early detection of treatable viral pathogens such as Herpes simplex virus (HSV), Cytomegalovirus (CMV), and Varicella-zoster virus (VZV) is essential for initiating appropriate therapies. However, multiplex PCRs for the rapid and simultaneous detection of these pathogens are scarce due to the complex PCR design and the elaborate validation process using cerebrospinal fluid samples. In this study, we established and validated a novel multiplex PCR assay for detecting HSV, CMV, and VZV in cerebrospinal fluid samples and implemented the assay on a fully automated platform.